Donor acute kidney injury and short-term graft outcome in renal transplantation - Jacobi, Johannes; Rebhan, Dirk; Heller, Katharina; Velden, Joachim; Hilgers, Karl Friedrich; Wullich, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Clinical Transplantation, 2014)
With increased waiting times for kidney transplantation, marginal organs from expanded criteria donors (ECD) are increasingly offered for allocation. In addition to ECD status, donors may have suffered from acute kidney injury (AKI) prior to organ procurement.In this retrospective cohort study, we studied short-term allograft function in 517 kidney transplants performed between the years 2008-2014. Recipients of allografts from deceased organ donors were categorized as standard criteria donors (SCD) or ECD with or without AKI defined by RIFLE criteria.Of 382 deceased donations, 174 (45.5%) were classified as ECD and 63 (16.5%) fulfilled AKI criteria. Donor creatinine on hospital admission was similar, whereas creatinine before organ procurement differed (p < 0.001). Despite these differences, serum creatinine and eGFR at discharge and after one yr showed only minor differences between kidneys with or without AKI. In multivariate linear regression analyses, donor AKI was not a predictor of one-yr allograft function.Given the poor prognosis of dialysis patients and the increase in waiting time, kidneys from SCD and ECD donors with AKI should be allocated for transplantation. In case of ECD donors with AKI, recipients should be informed about the possibility of permanent non-function or early graft loss.
EVALuna2:3714